1989
DOI: 10.1161/01.cir.79.5.1118
|View full text |Cite
|
Sign up to set email alerts
|

Effects of magnesium on the tone of isolated human coronary arteries. Comparison with diltiazem and nitroglycerin.

Abstract: To study the effects of magnesium (Mg2+) on human coronary arteries and to compare those effects with those of diltiazem and nitroglycerin, we measured the tension of ring segments from isolated human coronary arteries obtained at autopsy within 5 hours after death. Precontracted segments with 3 x 10(-6) M prostaglandin F2 alpha were studied after adding cumulative concentrations of these agents (1.0-8.0 mM, 10(-9)-10(-5) M, and 10(-10)-10(-6) M, respectively). Mg2+ significantly inhibited the tonic contractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…Low: ≤3 and high: >3. blood flow, vascular resistance, and capacitance function of vessels, which contributes to the pathoetiology of hypertension. [31][32][33][34] Additionally, Mg has shown its antioxidant benefits in the prevention of hypertension through attenuating the damage of vasculature from oxidative stress and preventing vascular injury. 5,6 Although accumulating evidence from such studies has indicated that low dietary or circulating Mg may be related to the development of hypertension because of its calcium antagonist and endothelial effects, 35 epidemiological evidence for a relationship between Mg intake and hypertension has been controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Low: ≤3 and high: >3. blood flow, vascular resistance, and capacitance function of vessels, which contributes to the pathoetiology of hypertension. [31][32][33][34] Additionally, Mg has shown its antioxidant benefits in the prevention of hypertension through attenuating the damage of vasculature from oxidative stress and preventing vascular injury. 5,6 Although accumulating evidence from such studies has indicated that low dietary or circulating Mg may be related to the development of hypertension because of its calcium antagonist and endothelial effects, 35 epidemiological evidence for a relationship between Mg intake and hypertension has been controversial.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, magnesium deficiencies can result in muscle weakness, cramping, and spasm (36). Also, magnesium inhibits tonic contraction of human coronary arteries (37), which could prevent coronary spasm (38) and, in turn, ischemic heart disease. Experimental studies have shown that low magnesium intake causes arrhythmias, such as supraventricular ectopy (39) and atrial fibrillation (40), which ultimately may explain the increased risk of sudden cardiac death associated with low magnesium (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review [29], none of the various circulating spasmogenic theories could satisfactorily account for coronary vasospasm in hyperthyroidism, and Miyagi et al [30] had shown magnesium to suppress coronary spastic angina. Evidently the potential for decreased magnesium to enhance coronary or cardiac reactivity to vasoactive agonists [31,32] deserves consideration in hyperthyroidism.…”
Section: Discussionmentioning
confidence: 99%